Essential cell biology : VOL.2 A practical approach - Davey, John; Ed. Lord, Mike; Ed (Oxford University Press, 2003)
Volume 1 of this two volume set focuses on techniques for studying cell structure. It describes light and electron microscopy, subcellular fractionation, protein purification and analysis, nucleic acid analysis, lipid analysis, and investigations of the cytoskeleton. Volume 2 concentrates on understanding how cells function. It describes a range of key investigations of cell function including analyses of gene expression, the cell cycle, cellular bioenergetics, transport across the nuclear membrane and the ER membrane, endosome transport, receptors, and signal transduction.